(untitled) (SOUTH ARAL SEA MEDICAL JOURNAL, 2025)
This article provides a description of microorganisms identified in the automicroflora of the skin of women from the Bukhara region at different age periods — premenopause, menopause, and postmenopause. For the study, the women were divided into three groups: Group 1 — premenopause, Group 2 — menopause, and Group 3 — postmenopause. Quantitative and qualitative differences in skin microorganisms compared to normal indicators were identified among the women in these groups.